2008
DOI: 10.1002/pssc.200779503
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet laser structuring of silicon carbide for cold cathode applications

Abstract: We present results of the first attempt to produce arrays of sharp Silicon Carbide (SiC) electron emitters by ultraviolet pulsed‐laser processing of single‐crystal SiC surfaces. This simple one‐step technique, performed under controlled pressure of a reactive gas, has demonstrated efficient silicon cold cathodes both in terms of current density and of emission threshold. SiC has been found to produce the best emitters when treated in air. The corresponding cathodes have a lower emission threshold and produce h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Because of the laser impact force, the remaining melted part was squeezed out from the pits and extruded each other, which finally formed a spike at the edge of melt pool. As the laser spot travelled under a designed track, a large number of spikes and pits occurred on the surface of No.3-No.6 samples, which were consistent with the reported experiment results [27,28]. Observed from No.5 and No.6 samples, the diameter of a single pit was around 40 µm, which implied that the laser ablation area was a little bigger than the laser spot.…”
Section: Analysis Of Surface Roughness Detection Resultssupporting
confidence: 88%
“…Because of the laser impact force, the remaining melted part was squeezed out from the pits and extruded each other, which finally formed a spike at the edge of melt pool. As the laser spot travelled under a designed track, a large number of spikes and pits occurred on the surface of No.3-No.6 samples, which were consistent with the reported experiment results [27,28]. Observed from No.5 and No.6 samples, the diameter of a single pit was around 40 µm, which implied that the laser ablation area was a little bigger than the laser spot.…”
Section: Analysis Of Surface Roughness Detection Resultssupporting
confidence: 88%
“…Excellent stability of SiCNW-based emitters has been also demonstrated in the study of Yang et al [75]. No obvious degradation of the current density (0.57 mA cm -2 ) was observed over 1200 min at an applied voltage value of 3000 V. Spanakis et al [76] presented results of the attempt to produce arrays of sharp SiC electron emitters by ultraviolet pulsedlaser processing of single-crystal SiC surfaces. This simple one-step technique, has demonstrated efficient SiC cold cathodes that have a lower turn-on field (1.8-2.2 V/μm) than their Si-based counterparts (2.7-3.3 V/μm) and that are able to yield higher current densities at a given operation voltage [76].…”
Section: Field Emission Cathodesmentioning
confidence: 73%
“…No obvious degradation of the current density (0.57 mA cm -2 ) was observed over 1200 min at an applied voltage value of 3000 V. Spanakis et al [76] presented results of the attempt to produce arrays of sharp SiC electron emitters by ultraviolet pulsedlaser processing of single-crystal SiC surfaces. This simple one-step technique, has demonstrated efficient SiC cold cathodes that have a lower turn-on field (1.8-2.2 V/μm) than their Si-based counterparts (2.7-3.3 V/μm) and that are able to yield higher current densities at a given operation voltage [76]. Moreover, Kim et al [77] reported the fabrication of, diode-type, field-emission-display (FED) devices with 3C-SiC NWs-based cathodes, which also demonstrated excellent FE properties at low applied voltages/electric fields and stable long-term performance.…”
Section: Field Emission Cathodesmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was carried out using a Jeol JSM-7000F field-emission microscope after sputter-coating each sample with a 20-nm-thick film of gold. Field emission current versus voltage ( I – U ) curves were acquired under high-vacuum conditions of 10 –3 Pa or lower in a planar diode system described in detail elsewhere . The substrate-to-anode distance was kept to 100 μm.…”
Section: Methodsmentioning
confidence: 99%